2019
DOI: 10.3892/ol.2019.10435
|View full text |Cite
|
Sign up to set email alerts
|

Integral analyses of survival‑related long non‑coding RNA MIR210HG and its prognostic role in colon cancer

Abstract: Colon cancer is the third most common cancer worldwide, and lymphatic metastasis is one of the principal factors affecting patient prognosis. Recent studies have revealed that long non-coding RNAs (lncRNAs) serve as important regulators in the pathogenesis of colon cancer, therefore affecting patient survival rates. In the present study, colon cancer-associated lncRNAs were screened based on their influence on patient survival. A number of survival-associated lncRNAs (and their potential mechanisms of action) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 36 publications
3
17
0
Order By: Relevance
“…In this study, we identified a novel function of MIR210HG in regulating the Warburg effect. In line with our result, RUAN et al showed that higher MIR210HG expression was associated with shorter overall survival in colon cancer and MIR210HG may play a role in the modulation of energy metabolism, especially glucose metabolism ( 48 ). Polysome profiling of HIF-1α mRNA showed reduced translation of HIF-1α in MIR210HG knockdown cells, suggesting the regulatory role if MIR210HG in HIF-1a translation process.…”
Section: Discussionsupporting
confidence: 92%
“…In this study, we identified a novel function of MIR210HG in regulating the Warburg effect. In line with our result, RUAN et al showed that higher MIR210HG expression was associated with shorter overall survival in colon cancer and MIR210HG may play a role in the modulation of energy metabolism, especially glucose metabolism ( 48 ). Polysome profiling of HIF-1α mRNA showed reduced translation of HIF-1α in MIR210HG knockdown cells, suggesting the regulatory role if MIR210HG in HIF-1a translation process.…”
Section: Discussionsupporting
confidence: 92%
“…MIR210HG was also demonstrated to facilitate progress of lung cancer [21], glioma [22], and hepatocellular carcinoma [23]. Moreover, two articles using bioinformatics methods identi ed MIR210HG was associated with poor OS of patients with colon cancer [24,25], which was in accordance with the results of our study. Our results imply potential functions of the ve immune-related lncRNA signature in the development of colon cancer, suggesting them as important biomarkers and therapeutic targets.…”
Section: Discussionsupporting
confidence: 91%
“…Of these six lncRNAs, MIR210HG is a common lncRNA that is highly expressed in a variety of tumors. In the 373 colon cancer patients, the 5-year survival rate of patients in the MIR210HG high expression group was lower than the 5-year survival rate of patients in the MIR210HG low expression group ( Ruan et al, 2019 ). In invasive breast cancer, MIR210HG is elevated in cancer tissues, and high MIR210HG expression is positively associated with a poor prognosis ( Li et al, 2019 ).…”
Section: Discussionmentioning
confidence: 84%